Falling Man: A Literatura em busca de possíveis significados para um espaço vazio - Mariano, Márcia Corrêa de Oliveira; Fernandes, Giséle Manganelli [UNESP] (My University, 2012)
September 11 has originated a wide range of artistic manifestations which have not only searched for plausible explanations for the tragedy, but also tried to review the events. In this sense, this paper aims at showing how a novel reevaluates this episode. The attacks made the United States experience a strong sense of vulnerability, triggering reactions from the American government, whose quick action was translated into a new national security strategy, associated with the war on terror. This paper analyzes the narrative strategies employed by the American author Don DeLillo in his novel Falling Man (2007) in order to reevaluate that tragedy. The debate of the topics is based on texts concerning the relationship between literature and history, postmodern fiction and issues on terrorism. This study contributes to enrich the discussion related to the events that led to the catastrophe and its aftermath, examining characters and groups linked to the September 11 terrorist attacks, revealing multiple truths subjected to social, ideological and historical conditions.

Os atentados de 11 de setembro originaram diversas manifestações artísticas buscando não apenas explicações para a tragédia, mas também tentando repensar os acontecimentos. Neste sentido, este trabalho apresenta uma investigação a respeito da maneira como um romance se apropriou desse episódio para reavaliá-lo. Com os ataques, os Estados Unidos experimentaram uma forte sensação de vulnerabilidade, desencadeando reações do governo americano, que formulou com bastante rapidez uma nova doutrina de segurança nacional, baseada no combate ao terrorismo. Este artigo analisa as estratégias narrativas utilizadas pelo autor americano Don DeLillo (2007a) no romance Falling Man, para reexaminar a tragédia. Textos teóricos e críticos sobre a relação entre Literatura e História, ficção Pós-Moderna e terrorismo fundamentam as discussões aqui apresentadas. Este estudo objetiva ampliar os questionamentos acerca dos fatos que levaram à catástrofe e suas consequências, examinando personagens e grupos ligados ao 11 de setembro, revelando múltiplas verdades, condicionadas social, ideológica e historicamente.
Falling Man: literature in search of possible meanings to an empty space
Keywords: Don DeLillo; Falling Man; 11 de setembro; Pós-Modernismo; Literatua e História